Thermal Comfort Level and the Ability of Trees to Reduce Temperature at H. Agus Salim Sports Hall, Padang City - Noril Milantara; Fauzan Fauzan; Jun Harbi; Lulu Yuningsih (Universitas Muhammadiyah Palembang, 2023)
Changes in land cover are thought to be the main factor in the Urban Heat Island (UHI) phenomenon. UHI is a form of local climate change which is characterized by an increase in temperature reaching 6oC in central urban areas compared to vegetated areas on the outskirts of the city. Compact vegetated land or Green Open Space (GOS), which is able to avoid increasing the surrounding temperature. GOR H. Agus Salim as one of the GOS in Padang City is a place for residents to have recreation and fill their free time by enjoying various culinary delights with friends and family as well as sports activities. This research aims to measure the benefits of tree canopies as climate amelioration in the H. Agus Salim GOR area. The research was conducted in September 2023, with 7 repetitions at 5 measurement points (3 under the tree canopy and 2 in the open field). Data is measured directly in the field with a thermohygrometer. The cooling effect provided by trees was analyzed using a difference approach between measurements in shade and open areas. Thermal comfort level is measured using the empirical formula Temperature Humidity Index (THI). The results showed that there was a decrease in temperature under the tree from 2,0oC (in the morning) to 2,9C (in the afternoon). However, THI calculations show that GOR H. Agus Salim is in the Uncomfortable criteria both under a canopy and in open areas.